The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.cam.2008.10.065
|View full text |Cite
|
Sign up to set email alerts
|

A globally convergent BFGS method with nonmonotone line search for non-convex minimization

Abstract: a b s t r a c tIn this paper, we propose a modified BFGS (Broyden-Fletcher-Goldfarb-Shanno) method with nonmonotone line search for unconstrained optimization. Under some mild conditions, we show that the method is globally convergent without a convexity assumption on the objective function. We also report some preliminary numerical results to show the efficiency of the proposed method.Crown

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Proof: From the very definition of the optimization scheme in [11] and [12], there exists an auxiliary parameter vectorq on D, and, clearly, max{U (q), k ≤ v} → U (q * ) as v → ∞. The proof now follows since U (q) ≤ U (q k ).…”
Section: B Frsmentioning
confidence: 89%
See 2 more Smart Citations
“…Proof: From the very definition of the optimization scheme in [11] and [12], there exists an auxiliary parameter vectorq on D, and, clearly, max{U (q), k ≤ v} → U (q * ) as v → ∞. The proof now follows since U (q) ≤ U (q k ).…”
Section: B Frsmentioning
confidence: 89%
“…An important feature of the MBFGS is that the function value at each iteration allows for an occasional decrease. Compared with some extant method in [12], the MBFGS can converge to a local optimal point without a convex assumption on the objective function. Additionally, the MBFGS can be considered as an extension of the method in [13] to the nonmonotone scheme.…”
Section: B Frsmentioning
confidence: 96%
See 1 more Smart Citation
“…Their modifications were so useful that have motivated many researchers to make further improvements on the BFGS method. For example, Xiao et al introduced a new algorithm by using the MBFGS update formula suggested by Li and Fukushima along with a nonmonotone line search proposed in [23]. They proved that the method is globally convergent for nonconvex optimization problems.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, a nonmonotone MBFGS algorithm is introduced and the global convergence of the method is proved without convexity assumption. Actually, the algorithm combines the MBFGS method, proposed by Xiao et al in [23], with nonmonotone line search (5) and also gains advantages of [2] and [24]. Numerical experiments indicate that the new algorithm is promising and efficient.…”
Section: Introductionmentioning
confidence: 99%